An Analysis of the Money Demand Function for Zambia: A Gregory Hansen Cointegration Approach - Mumba, Peter Nsokolo; Ziramba, Emmanuel (Journal of Economics and Behavioral Studies, 2021)
The objective of this study was to analyze the money demand function for Zambia for the period 1978 – 2018 using annual time series data. The study employed the Gregory Hansen cointegration technique. The study also employed Hendry’s General to Specific technique to estimate the error correction model by obtaining a parsimonious model. The results of the Gregory Hansen test confirmed the presence of a cointegrating relationship and selected the GH-2 model as the most plausible model with a level shift and a trend. The results also endogenously determined 1994 as the break year in the money demand function. Other interesting results obtained by the study suggest that inflation and interest rate are the robust determinants of real money demand both in the short and long run. Furthermore, unlike many other developing countries, the results show that money is a necessity in Zambia. The other interesting results suggested by the study are that the financial sector reforms of 1994 diminished the demand for real money; however, the positive time trend suggests that there has been an increase in real money holdings over time in Zambia. The low-interest elasticity of money demand also potentially compromises the effectiveness of money supply as a monetary policy tool for economic stabilization. The results of the CUSUM and CUSUMSQ confirm the stability of the money demand function in Zambia.